Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation dalam Pembelajaran Bahasa Arab di Program Studi Pendidikan Agama Islam (PAI) STAI Syekh Manshur Pandeglang - Euis Ernawati (CV. Creative Tugu Pena, 2024)
Students' diverse educational backgrounds often cause problems in learning activities. Students who have previously studied and mastered basic Arabic material tend to feel bored in subject of Arabic I. Meanwhile, students who have never studied Arabic find it difficult to understand the material. For this reason, an appropriate learning model is needed so that all students become more active in discussions and can better understand Arabic I material. This research aims to describe the application of the group investigation type of cooperative learning model in Arabic language learning in the STAI Syekh Manshur Islamic Religious Education Study Program and problems that occur in learning. The research uses qualitative approach with descriptive analysis.. The research subjects were first semester students who took Arabic I subject. Data collection took the form of interviews and document analysis as data triangulation. The results of the research show that the application of the group investigation type cooperative learning model is quite effective in learning Arabic I in the Islamic Religious Education Study Program. There are several problems that occur in implementing the group investigation type cooperative learning model in Arabic language learning in the Islamic Religious Education study program, namely: first, this learning model takes a lot of time so it requires good time management. secondly, the contribution of students with low abilities is still lacking and they tend to rely on other students who are smart.